Analytical modelling of planar potential and current distributions in electrodes of lithium-Ion batteries - Adair, D.; Hara, Toru; Massalin, Y.; Ismailov, K.; Bakenov, Zhumabay (Analytical modelling of planar potential and current distributions in electrodes of lithium-Ion batteries, 2015)
Mathematical modelling can play an important role in the design of a lithium-ion cell in that many design iterations can be performed at relatively little cost. • Electrochemical models are useful for cell design and optimization but can be typically high-order and complex and hence computationally expensive, and, are therefore not suitable for real-time applications. • Much reduced order electrochemical models for lithium-ion cells have been developed, with these type of models more suitable for use with real-time on-board electronic control units. • However, a difficulty with these methods is that the current-voltage behavior for different operating conditions cannot be predicted.
Keywords: analytical modelling; electrodes of lithium-Ion batteries